A colon-specific prodrug of metoclopramide ameliorates colitis in an experimental rat model - Yang Y; Kim W; Kim D; Jeong S; Yoo JW; Jung Y (Dove Medical Press, 2018)
Yejin Yang,* Wooseong Kim,* Dayoon Kim, Seongkeun Jeong, Jin-Wook Yoo, Yunjin Jung College of Pharmacy, Pusan National University, Busan 609-735, South Korea *These authors contributed equally to this work Background: We examined whether metoclopramide (MCP), a modulator of dopamine and serotonin receptors, alleviated colitis and had synergistic effects when coadministered with 5-aminosalicylic acid (5-ASA) in an experimental model of colitis. Methods: MCP azo-linked to 5-ASA (5-[4-chloro-2-{2-(diethylamino)ethylcarbamoyl}–1-methoxyphenyl]azosalicylic acid, MCP-azo-ASA) was synthesized, where 5-ASA was used as a colon-targeting carrier and an anti-colitic agent, and the ability of MCP-azo-ASA to target the colon in vitro and in vivo was evaluated. Results: Our results indicate that MCP-azo-ASA was cleaved to MCP and 5-ASA in the cecal contents, but not in the contents of the small intestine. Oral gavage with equimolar concentrations of MCP-azo-ASA and sulfasalazine (SSZ, a colon-specific prodrug of 5-ASA widely used clinically) demonstrated that the two prodrugs delivered comparable amounts of 5-ASA to the cecum. MCP was barely detected in the blood after oral gavage with MCP-azo-ASA. In a rat model of 2,4-dinitrobenzene sulfonic acid hydrate (DNBS)-induced colitis, MCP-azo-ASA alleviated colonic damage in a dose-dependent manner. Moreover, MCP-azo-ASA reduced the concentrations of inflammatory mediators in the inflamed colon. At low equimolar doses, MCP-azo-ASA, but not SSZ, resulted in significant anti-colitic effects, which indicates that MCP has anti-colitic activity. MCP-azo-ASA had anti-colitic effects equal to those of SSZ at high equimolar doses. Conclusion: Thus, our results indicate that MCP-azo-ASA is a colon-specific prodrug of MCP. Targeted delivery of MCP to the colon ameliorated DNBS-induced colitis in rats, and we did not observe any synergistic effects of MCP after co-delivery with 5-ASA. Keywords: metoclopramide, 5-aminosalicylic acid, colon-specific prodrug, colitis, serotonin, dopamine